Alaskacladius gen. nov., (Diptera: Chironomidae), a unique new orthoclad from Alaska - Namayandeh, Armin; Hudson, Patrick L.; Ghaderi, Edris; Vasquez, Adrian A.; Ram, Jeffrey L. (Zootaxa, 2023)
We describe a new genus Alaskacladius gen. nov., based on the adult stages collected from Alaska, USA, and British Columbia, Canada. Molecular and morphological assessment of adult specimens supports the presence of a new genus. Alaskacladius gen. nov., is related to the genera Doithrix Sæther & Sublette, 1983; Georthocladius Strenzke, 1941; Parachaetocladius Wülker, 1959; and Pseudorthocladius Goetghebuer, 1932. Based on the molecular analysis result and intergeneric K2P distance obtained from Cytochrome Oxidase I (COI) genes, Alaskacladius is closest and forms a sister group with Doithrix.